2018
DOI: 10.1016/j.jid.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Genetic Variants Associated with Melanoma BRAF/NRAS Subtypes

Abstract: BRAF and NRAS mutations arise early in melanoma development, but their associations with low-penetrance melanoma susceptibility loci remain unknown. In the Genes, Environment and Melanoma Study, 1,223 European-origin participants had their incident invasive primary melanomas screened for BRAF/NRAS mutations and germline DNA genotyped for 47 single-nucleotide polymorphisms identified as low-penetrant melanoma-risk variants. We used multinomial logistic regression to simultaneously examine each single-nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(88 reference statements)
0
8
0
1
Order By: Relevance
“…Evidence suggests that histological factors may affect tumour aggressiveness and patient prognosis in melanoma and KCs . One study, for example, found that two SNVs in IRF4 and PLA2G6 were associated with BRAF / NRAS melanoma subtypes . However, PRS studies to date have combined histological subtypes together, which could lead to confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that histological factors may affect tumour aggressiveness and patient prognosis in melanoma and KCs . One study, for example, found that two SNVs in IRF4 and PLA2G6 were associated with BRAF / NRAS melanoma subtypes . However, PRS studies to date have combined histological subtypes together, which could lead to confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous melanomas are categorized byfourgenomicsubtypes: mutant BRAF, mutant RAS(mainly NRAS), mutant NF1, and triple-wild-type. In one study, germline DNAfrom 1,223 participantswas genotyped for 47 SNVs previously associated with melanoma risk [53]. Melanomas were also interrogated for BRAFand NRASmutations.…”
Section: Germline Variant By Somatic Mutation (Gxm) Associationin Transmentioning
confidence: 99%
“…The rs12203592(T)alleleof IRF4was associated with decreased risk of BRAF V600E and BRAF V600K mutations, but an increased likelihood ofother BRAFexon 15 mutations (Table 2). The rs132985(T) allele of PLA2G6was associated with increased likelihood of BRAF V600E and other BRAFexon 15 mutations(Table 2) [53] Germline MC1Rvariantsalso influence the somaticmutational landscape of melanoma. These variants are associated with red hair, freckling, and sun sensitivity.…”
Section: Germline Variant By Somatic Mutation (Gxm) Associationin Transmentioning
confidence: 99%
“…Около 25% всех злокачественных опухолей имеют нарушения регуляции сигнального каскада MAPK, связанные с увеличением продукции активирующих лигандов, а также наличием активирующих мутаций в генах семейств RTKs, RAS и RAF [3]. При меланоме кожи нарушения в MAPK сигнальном каскаде связаны, как правило, с активирующей мутацией в гене BRAF в 50% случаев или с мутацией в гене NRAS в 15% случаев [4]. Данный факт демонстрирует важность контроля регуляции MAPK в гомеостазе меланоцитов.…”
Section: Introductionunclassified